Retain responsible Liberal government in Victoria : 1 Jeff Kennett, Liberal Burwood, Legislative Assembly. - Liberal Party of Australia. Victorian Division (Camberwell, [Vic.] : [Liberal Party], 1976)
Poster advertising Liberal candidate for Burswood Jeff Kennett for the Victorian state election held 20 March 1976. Features portrait of a smiling Kennett wearing a white rollnecked jumper. "Saturday 20th March 1976" appears above the title. "Authorised by, G. Harris, 4 Mabel St., Camberwell" appears at the foot of the poster.
Caption title.
National Library of Australia's copy has small stain adjacent "1" in the title. Crop marks visible in corners.
Digital master available
Keywords: Kennett, Jeff -- Posters; Victoria. -- Parliament. -- Legislative Assembly -- Elections, 1976 -- Posters; Politicians -- Victoria -- Posters; Posters, Australian; Australia -- Posters; Australian